Pebax Polymer Inclusion Hydrophobic Deep Eutectic Solvent Membranes for Pervaporation of Biobutanol: Mass Transfer and Cosmo-Rs Analysis - Zuniga-Navarro, G; Quijada-Maldonado, E; Olea-Chandia, F (Elsevier B.V., 2024)
Deep Eutectic Solvent(DES) and specifically Hydrophobic Deep Eutectic Solvents (HDES) are considered a relatively novel class of solvents, which show good features to include them in pervaporation membranes. Polymer inclusion HDES membranes offer a separation media, which shows a faster molecular diffusion than polymeric membranes, combining the best properties of liquid and polymer membranes, such a high selectivity with high burst pressure and durability. The aim of this work focuses on the development of different PEBAX/ lidocaine-thymol [2:1] (Lidol HDES) membranes by the temperature-induced phase-inversion technique to be used in the pervaporation process to recover butanol from ABE model solution. The mass transfer modeling through the membrane using the resistances-in-series approach was implemented to find the mass transfer resistance distribution. The polymer inclusion membranes showed improved results for the butanol/water selectivity compared to the single PEBAX membrane used as a reference. The flux of butanol obtained with the 30 % w/w Lidol HDES membrane was 0.112 kg m−2 hr−1. The flux of water was 0.445 kg m−2 hr−1 showing a selectivity value for butanol/water of 20 % bigger than single PEBAX membrane. The improvement in the selectivity can be explained by the synergic effect of the HDES in the membrane. After use, the polymer inclusion membrane consistently demonstrated a stable performance in effectively separating butanol from the ABE solution. It was seen that the overall resistance decreases as the liquid flow rate increases; regarding the liquid side resistance, it becomes important at smaller flow rates and is almost negligible for turbulent regimen. © 2023 Elsevier B.V.